A field example of free surface testing - Bodvarsson, Gunnar; Zais, Elliot (A field example of free surface testing, 1978)
Theoretical results on free liquid surface dynamics presented by Bodvarsson (1978, this volume), provide the basis for a technique of reservoir probing and testing which can yield results that are supplementary to conventional well testing data. The Laugarnes geothermal area in Iceland which is one of the sources of the Reykjavik District Heating System is a case where both methods are applicable and appear interestingly, to yield quite different results. A brief account of the free surface results is presented.